Strategies for timely evaluation of genebank accessions - Koo, Bonwoo; Wright, Brian D. (International Food Policy Research Institute, 2003)
The importance of plant genetic resources as building blocks for crop improvement has grown with recent advances in biotechnology and scientific information. The lack of useful data about accessions is frequently cited as an obstacle to greater utilization of genebanks by plant breeders (Wright 1997). In this context, we can invoke again the analogy to a library for the importance of relevant information, as discussed in Brief 7. If there are no data on the title, key-word, or other relevant information about the books held in the library, they will rarely be used, and the value of the library will be small.